1997
DOI: 10.2307/3870575
|View full text |Cite
|
Sign up to set email alerts
|

The Dominant Developmental Mutants of Tomato, Mouse-ear and Curl, Are Associated with Distinct Modes of Abnormal Transcriptional Regulation of a Knotted Gene

Abstract: The Curl (Cu) and Mouse-ear (Me) mutations of tomato cause two seemingly unrelated developmental syndromes with a wide range of pleiotropic phenotypes. Yet, the distinct morphogenic alterations in shoots, leaves, and inflorescences conferred by the two mutations appear to be caused by unchecked meristematic activity that characterizes dominant mutations in Knotted1 (Kn1)-like genes of monocot plants. We have been unable to separate the two closely linked Cu and Me mutations, and they may lie in the same gene. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 0 publications
4
49
0
1
Order By: Relevance
“…Among the best studied of these are the MADS-box family of genes that control floral-organ identity (Pnueli et al 1991(Pnueli et al , 1994a and the knotted1-like homeobox (KNOXI) genes that regulate leaf morphogenesis (Avivi et al 2000;Janssen et al 1998;Chen et al 1997;Parnis et al 1997;Hareven et al 1996). Moreover, a large number of loci affecting vegetative and floral morphology have been identified through mutant analysis (Stevens and Rick 1986).…”
Section: Correspondence Of Qtl To Known Mutant Loci In Tomatomentioning
confidence: 99%
“…Among the best studied of these are the MADS-box family of genes that control floral-organ identity (Pnueli et al 1991(Pnueli et al , 1994a and the knotted1-like homeobox (KNOXI) genes that regulate leaf morphogenesis (Avivi et al 2000;Janssen et al 1998;Chen et al 1997;Parnis et al 1997;Hareven et al 1996). Moreover, a large number of loci affecting vegetative and floral morphology have been identified through mutant analysis (Stevens and Rick 1986).…”
Section: Correspondence Of Qtl To Known Mutant Loci In Tomatomentioning
confidence: 99%
“…However, KNOX1 expression is reestablished later in the developing primordia of compound leafed plants (12)(13)(14)(15). Additionally, overexpression of KNOX1 genes in transgenic tomato plants or spontaneous tomato mutants results in leaves with increased numbers of leaflets (13,14,16). Therefore, it has been concluded that KNOX1 genes are involved in compound leaf formation by establishing an indeterminate environment within developing primordia.…”
mentioning
confidence: 99%
“…Subsets of these genes are essential for meristem maintenance and lateral organ formation in all higher plants (Burglin 1997;Sharma and Fletcher 2002). Ectopic expression of KNOX genes in various plants causes drastic alteration in leaf and Xower morphogenesis in spontaneous mutants (Smith et al 1992;Chen et al 1997;Parnis et al 1997) and dwarWsm and loss of apical dominance in transgenic plants (Matsuoka et al 1993;Sinha et al 1993;Lincoln et al 1994;Chuck et al 1996;Chen et al 1997;Parnis et al 1997). Alterations in morphology caused by ectopic expression of KNOX genes were also accompanied by hormone level changes.…”
Section: Discussionmentioning
confidence: 95%